Discovery of necrosis avidity of rhein and its applications in necrosis imaging. (20th October 2020) - Zhang, Dongjian; Jin, Qiaomei; Ni, Yicheng; Zhang, Jian
Abstract: Necrosis-avid agents possess exploitable theragnostic utilities including evaluation of tissue viability, monitoring of therapeutic efficacy as well as diagnosis and treatment of necrosis-related disorders. Rhein (4, 5-dihydroxyl-2-carboxylic-9, 10-dihydrodiketoanthracene), a naturally occurring monomeric anthraquinone compound extensively found in medicinal herbs, was recently demonstrated to have a newly discovered necrosis-avid trait and to show promising application in necrosis imaging. In this overview, we present the discovering process of rhein as a new necrosis-avid agent as well as its potential imaging applications in visualisation of myocardial necrosis and early evaluation of tumour response to therapy. Moreover, the molecular mechanism exploration of necrosis avidity behind rhein are also presented. The discovery of necrosis avidity with rhein and the development of rhein-based molecular probes may further expand the scope of necrosis-avid compounds and highlight the potential utility of necrosis-avid molecular probes in necrosis imaging.